Towards Reuse on the Meta-Level - Wirkner, Dominic; Boßelmann, Steve (Electronic Communications of the EASST, 2018)
Modern software development peaks in complex product lines and utilizes features of programming languages to their extend. On the other hand, model driven development shines by abstraction from implementation details to ease communication between programmers and domain experts. With the CINCO meta tooling suite there is now a framework to factor out programming knowledge completely in that it allows creating domain specific graphical modeling environments. Bundled with capabilities of full code generation domain experts can create software with minimum effort. In this paper an extension to the language family of CINCO is introduced which acts as one part of a foundation for developing software product lines. It highly stretches reuse of model specifications to overcome reoccurring problems in the context of inter-model references.